Enterprise Systems Enabling Smart Commerce - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 2014)
Smart commerce is an evolution of ecommerce that aims at providing an enhanced and holistic customer experience by tying together cloud, social media, analytics, and back-end enterprise systems. With the emergence of service-oriented architectures (SOA), enterprise systems functionality has become available as enterprise services that can be provided on-demand via the Internet. Mobile access to enterprise systems via smart phones and tablets has created new opportunities for enhancing customer value. In order to fully leverage these developments, organizations must develop new solutions that extend existing enterprise systems by integration of enterprise systems with mobile devices and other applications. In this paper, we present a prototype smart commerce solution that demonstrates the use of a composite application that integrates the order process in SAP ERP with mobile device, cloud, social media and analytics.